Thanks but No Thanks: A New Policy to Reduce Land Conflict - Martin Dufwenberg; Gunnar Köhlin; Peter Martinsson; Haileselassie Medhin (Center for Economic Studies and ifo Institute (CESifo), 2014)
Land conflicts in developing countries are costly. An important policy goal is to create respect for borders. This often involves mandatory, expensive interventions. We propose a new policy design, which in theory promotes neighborly relations at low cost. A salient feature is the option to by-pass regulation through consensus. The key idea combines the insight that social preferences transform social dilemmas into coordination problems with the logic of forward induction. As a first, low-cost pass at empirical evaluation, we conduct an experiment among farmers in the Ethiopian highlands, a region exhibiting features typical of countries where borders are often disputed. Our results suggest that a low-cost land delimitation based on neighborly recognition of borders could deliver a desired low-conflict situation if accompanied by an optional higher cost demarcation process.
Keywords: C78; C93; D63; Q15; 330; conflict; land-conflict game; social preferences; forward induction; Ethiopia; experiment; land reform